ADVANCES IN NANOTECHNOLOGY FOR IMPROVED NUTRACEUTICALS- AN OVERVIEW (International Journal of Food and Nutritional Sciences, 2022)
Nanotechnology is one of the revolutionizing fields which can provide long-lasting solutions to many areas of human health including food, nutrition and medicine. With the increase in population, there is a great demand for more value-added food and nutraceuticals. Therefore researchers have turned to nanotechnology to provide better solutions to these fields. Some of these techniques include the study of characterization of nanomaterials, engineered nanomaterial-based delivery systems bioavailability of the nutritional compounds in food substances, etc. Very few nanotechnology-based nutraceuticals and dietary products are available in the market. However, extensive study needs to be carried out on the use of nanotechnology for improved nutraceuticals by commercializing to satisfy consumers. Nutraceuticals have gained considerable interest due to their safety and therapeutic effects. In recent years, nanoformulations have been rising interest in nutraceuticals. Therefore in the present review article, we have focused on the applications of nanotechnology toward improved nutraceuticals. The article gives a comprehensive outline of the various techniques employed for enhancing the nutrition quality, bioavailability and stability of nutraceuticals.